Effects of Enlarged Adenoids on Middle Ear Pressure and Hearing - Alam, Md Noor Kutubul; Huque, SM Nazmul; Hossain, ABM Delowar; Atikuzzaman, Kazi; Hussain, Mohammad Jamal; Arefin, Mostafa Kamal (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Adenoids are common childhood upper respiratory tract problem which frequently obstruct the nasopharyngeal opening with tubal occlusion causes reduction in middle ear pressure with conductive hearing loss. Objective: To observe middle ear pressure and level of hearing in children with enlarged adenoids. Methods: This cross sectional observational study conducted among 72 children of enlarged adenoids admitted or attended in Dhaka Medical College Hospital and Bangabandhu Sheikh Mujib Medical University Dhaka. Results: 72 children of enlarged adenoids of age ranges between 5-12 years with male female ratio was 1.25:1. Mouth breathing (65.27%), hearing impairment (59.72%), nasal obstruction (55.55%) and snoring (56.94%) were the presenting symptoms of the patients. Majority of the patients of this study came from middle class (52.77%). Most of the patients with enlarged adenoids were grossly enlarged (51.38%). 43.05% grossly enlarged adenoids had significant hearing loss . In this series 65 ears (45.13%) had type A Tympanogram. 58 ears (40.27%) has Type B Tympanogram and 21 ears (14.58%) has Type C Tympanogram. Conclusion: This study revealed significant association between enlarged adenoids and conductive hearing loss of variable degree and negative middle ear pressure. Bangladesh J Otorhinolaryngol; April 2021; 27(1): 73-80